Incidence of intra-procedural complications according to the timing of endovascular treatment in ruptured intracranial aneurysms - Gaudino, Chiara; Navone, Stefania Elena; Da Ros, Valerio; Guarnaccia, Laura; Marfia, Giovanni; Pantano, Patrizia; Peschillo, Simone; Triulzi, Fabio Maria; Biraschi, Francesco (Frontiers in Neurology, 2023)
Background Although endovascular treatment of ruptured intracranial aneurysms is well-established, some critical issues have not yet been clarified, such as the effects of timing on safety and effectiveness of the procedure. The aim of our study was to analyze the incidence of intra-procedural complications according to the timing of treatment, as they can affect morbidity and mortality. Materials and methods We retrospectively analyzed all patients who underwent endovascular treatment for ruptured intracranial aneurysms at three high flow center. For all patients, imaging and clinical data, aneurysm's type, mean dimension and different treatment techniques were analyzed. Intra-procedural complications were defined as thrombus formation at the aneurysm's neck, thromboembolic events, and rupture of the aneurysm. Patients were divided into three groups according to time between subarachnoid hemorrhage and treatment (<12 h hyper-early, 12–36 h early, and >36 h delayed). Results The final study population included 215 patients. In total, 84 patients (39%) underwent hyper-early, 104 (48%) early, and 27 (13%) delayed endovascular treatment. Overall, 69% of the patients were treated with simple coiling, 23% with balloon-assisted coiling, 1% with stent-assisted coiling, 3% with a flow-diverter stent, 3% with an intrasaccular flow disruptor device, and 0.5% with parent vessel occlusion. Delayed endovascular treatment was associated with an increased risk of total intra-procedural complications compared to both hyper-early (p = 0.009) and early (p = 0.004) treatments with a rate of complications of 56% (vs. 29% in hyper-early and 26% in early treated group—p = 0.011 and p = 0.008). The delayed treatment group showed a higher rate of thrombus formation and thromboembolic events. The increased risk of total intra-procedural complications in delayed treatment was confirmed, also considering only the patients treated with simple coiling and balloon-assisted coiling (p = 0.005 and p = 0.003, respectively, compared to hyper-early and early group) with a rate of complications of 62% (vs. 28% in hyper-early and 26% in early treatments—p = 0.007 and p = 0.003). Also in this subpopulation, delayed treated patients showed a higher incidence of thrombus formation and thromboembolic events. Conclusions Endovascular treatment of ruptured intracranial aneurysms more than 36 h after SAH seems to be associated with a higher risk of intra-procedural complications, especially thrombotic and thromboembolic events.